Depositional environment and hydrocarbon potential of the Oligocene Menilite Formation in the Western Carpathians: A case study from the Loučka section (Czech Republic). (September 2019) - Jirman, Petr; Geršlová, Eva; Bubík, Miroslav; Sachsenhofer, Reinhard F.; Bechtel, Achim; Więcław, Dariusz
Abstract: The Eocene-Oligocene boundary in the Paratethys area represents a period associated with a major extinction event followed by anoxic events. A good understanding of the factors controlling the formation of organic-rich layers is a key for prediction of source rock distributions. An excellent opportunity to study these factors is provided by the Loučka section situated in the Silesian Unit of the Czech Republic. The Menilite Formation is subdivided into the Subchert Member, Chert Member, Dynów Marlstone and Šitbořice Member and comprises non-calcareous shales, marlstones and cherts. The lithological variations reflect strongly depositional environment, which caused strong changes in geochemical parameters and source rock potential. The ratio of total organic carbon to total sulphur (TOC/TS) and methylated 2-methyl-2 (trimethyltridecyl) chroman (MTTC) ratios supported by paleontological evidence show normal marine to brackish water conditions. Pr/Ph ratios indicate strictly anoxic conditions during deposition of the upper part of the Subchert Member and the lower part of the Chert Member. Very low steranes/hopanes ratios reflect strong bacterial activity during deposition of the Chert Member. Very high HI values (>600 mg HC/g TOC) and the apparent absence of terrestrial macerals suggest that high amounts of C29 steranes and long-chain n-alkanes in this member result from the input of algal material. The Menilite Formation contains mainly type II kerogen and typically holds a "good" source rock potential. HI values > 600 mg HC/g TOC are observed in the Chert Member, while values < 250 mg HC/g TOC occur in some low TOC samples from the base of the Subchert Member. Tmax and low homohopane ratios confirm that the organic matter is immature. The source potential index (SPI) of the entire succession of the Menilite Formation is about 1.25 t HC/m 2, which is significantly lower than SPI determined for the Polish and Ukrainian Carpathians, but mainly due to the lower thickness. Highlights: The prevailing kerogen in the Menilite Fm. is type II classified as "good" or "very good" source rock. Very low steranes/hopanes ratios reflect strong bacterial activity during deposition of the Chert Member. Changes in redox and salinity within the Loučka section show same pattern as observed in the Austrian Molasse Basin. The high C29 steranes are not related to terrestrial organic matter but alginite maceral.